2021
DOI: 10.19102/icrm.2021.120903
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronavirus Disease 2019 on Cardiac Arrhythmia Care: Experience of a Spanish Tertiary Hospital During the Health Crisis Triggered by the First Wave of the Pandemic

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has resulted in a deep restructuring of cardiovascular care, especially in the setting of cardiac arrhythmia units, which are characterized by a wide variety of clinical and interventional activities. We describe the experience of a large university hospital deeply hit during the COVID-19 health crisis (first outbreak of the pandemic), focusing on the exceptional measures implemented and their impact in terms of outcomes. We performed a retrospective study compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Reports confirm that regular outpatients and patients with sudden illnesses have also shown signs of giving up treatment. According to a report by the Spanish health system [ 6 ], during COVID-19 (Mar 16, 2020, to Mar 22, 2020), the number of patients treated for ST-elevation myocardial infarction decreased by 40%. Another study reported that in the early stage of the pandemic in the United States, the number of visits to the emergency department was significantly lower than that in the same period in 2019 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports confirm that regular outpatients and patients with sudden illnesses have also shown signs of giving up treatment. According to a report by the Spanish health system [ 6 ], during COVID-19 (Mar 16, 2020, to Mar 22, 2020), the number of patients treated for ST-elevation myocardial infarction decreased by 40%. Another study reported that in the early stage of the pandemic in the United States, the number of visits to the emergency department was significantly lower than that in the same period in 2019 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%